2016
DOI: 10.1007/s11136-016-1326-2
|View full text |Cite
|
Sign up to set email alerts
|

Phenylketonuria patients’ and their parents’ acceptance of the disease: multi-centre study

Abstract: PurposePhenylketonuria (PKU) still poses a therapeutic challenge for patients and medical professionals. The aim of the study was to assess both patients’ and their parents’ acceptance of the disease.MethodsThe study included 218 PKU patients and 178 parents of PKU children who were enrolled in the study on the basis of questionnaire data.ResultsRegarding attitude towards the disease, our study demonstrated that 63 (28.9 %) PKU patients did not accept the disease. Patients who found accepting the disease diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
5
0
4
Order By: Relevance
“…Jak wynika z badań rodziców dzieci, u których wczesną diagnozę i skuteczną terapię wprowadzono już w okresie noworodkowym, rozpoznanie IEM nadal pozostaje silnym i długotrwałym czynnikiem traumatyzującym [14][15][16]. Badania potwierdzają, że emocjonalne reakcje rodziców na diagnozę mają tendencję do tego, by pozostawać stałymi w czasie [14][15][16][17]. Należy podkreślić, że brak akceptacji choroby dziecka przez opiekunów często utrzymuje się przez wiele lat od postawienia diagnozy i może nasilać się u rodziców nastoletnich pacjentów nawet w przypadku skutecznej terapii, np.…”
Section: Jakość żYcia Rodziców Dzieci Przewlekle Chorychunclassified
See 3 more Smart Citations
“…Jak wynika z badań rodziców dzieci, u których wczesną diagnozę i skuteczną terapię wprowadzono już w okresie noworodkowym, rozpoznanie IEM nadal pozostaje silnym i długotrwałym czynnikiem traumatyzującym [14][15][16]. Badania potwierdzają, że emocjonalne reakcje rodziców na diagnozę mają tendencję do tego, by pozostawać stałymi w czasie [14][15][16][17]. Należy podkreślić, że brak akceptacji choroby dziecka przez opiekunów często utrzymuje się przez wiele lat od postawienia diagnozy i może nasilać się u rodziców nastoletnich pacjentów nawet w przypadku skutecznej terapii, np.…”
Section: Jakość żYcia Rodziców Dzieci Przewlekle Chorychunclassified
“…Należy podkreślić, że brak akceptacji choroby dziecka przez opiekunów często utrzymuje się przez wiele lat od postawienia diagnozy i może nasilać się u rodziców nastoletnich pacjentów nawet w przypadku skutecznej terapii, np. dietetycznej, oraz braku objawów klinicznych [16,17]. Badania przeprowadzone na dużej grupie rodziców dzieci chorych na fenyloketonurię (phenylketonuria -PKU) wykazały, że akceptacja choroby ma zasadniczy wpływ na integrację społeczną i postrzeganie możliwości edukacyjnych dzieci oraz ich przyszłej sytuacji zawodowej [17].…”
Section: Jakość żYcia Rodziców Dzieci Przewlekle Chorychunclassified
See 2 more Smart Citations
“…4 Acceptance of a PKU diagnosis by patients and subsequent adherence to the low natural protein diet is well documented in the literature to be difficult. [4][5][6][7][8][9] A 2016 publication by Witalis et al 5 documented that 63% of children aged between 2 and 10 years and 49% of parents struggled to accept a diagnosis of PKU. A later publication by Witalis et al (2017) further investigating the knowledge and attitudes of parents and children reported that 22% of parents and 30% of children had a sense of helplessness with the daily complexities of trying to implement the low natural protein diet.…”
Section: Introductionmentioning
confidence: 99%